The impact of tracheostomy timing (early & late) on severe head injury patients toward clinical outcomes - Mohamed Ludin, Salizar (International Council of Nursing, 2023)
Severe head injury patients require a specific treatment plan and nursing care to achieve an optimal clinical outcome while mild head injury patients may need a few days of hospitalisation for close monitoring and conservative medical administrations. However, in severe head injury cases, the patients may require a more extended period of hospitalisation for a series of complex neuro-medical and neurosurgical management. Tracheostomy may be performed on head injury patients with protracted breathing problems. Early tracheostomy (ET) may improve clinical outcomes late tracheostomy. ET is defined as the tracheostomy done seven days after the initiation of endotracheal intubation.